2012
DOI: 10.1371/journal.pone.0038525
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pregabalin and the Glial Attenuator Minocycline on the Response to Intradermal Capsaicin in Patients with Unilateral Sciatica

Abstract: BackgroundPatients with unilateral sciatica have heightened responses to intradermal capsaicin compared to pain-free volunteers. No studies have investigated whether this pain model can screen for novel anti-neuropathic agents in patients with pre-existing neuropathic pain syndromes.AimThis study compared the effects of pregabalin (300 mg) and the tetracycline antibiotic and glial attenuator minocycline (400 mg) on capsaicin-induced spontaneous pain, flare, allodynia and hyperalgesia in patients with unilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…A recent study showed that minocycline attenuated hyperalgesia in a small cohort of patients with sciatica 128 . Ibudilast also showed signs of efficacy in relieving pain associated with painful diabetic neuropathy and complex regional pain syndrome 126 .…”
Section: Clinical Evidence For the Neuroimmune Interfacementioning
confidence: 99%
“…A recent study showed that minocycline attenuated hyperalgesia in a small cohort of patients with sciatica 128 . Ibudilast also showed signs of efficacy in relieving pain associated with painful diabetic neuropathy and complex regional pain syndrome 126 .…”
Section: Clinical Evidence For the Neuroimmune Interfacementioning
confidence: 99%
“…Minocycline has also shown promise in studies of pain, particularly in an animal model of morphine effects. Though minocycline has nonselective actions at both neuronal and glial cell types within the nervous system [219], its anti-inflammatory actions are theorized to be a result of its inhibitory influence on the latter [220,221]. Studies have shown this tetracycline antibiotic microglial inhibitor to reduce negative aspects of morphine treatment (respiratory depression, tolerance, and reward) while augmenting analgesia [213,222].…”
Section: Glial Targetsmentioning
confidence: 99%
“…Furthermore, minocycline has been shown to be beneficial in pain states such as rheumatoid arthritis (Langevitz et al, 2000) and sciatica (Sumracki et al, 2012). Both systemic and central administration of minocycline has been shown to prevent microglial activation and release of pro-inflammatory cytokines/mediators, and consequently the development of nerve injury-induced allodynia in several models (Raghavendra et al, 2003, Zanjani et al, 2006, Guasti et al, 2009, Pu et al, 2013, LeBlanc et al, 2011, Wei et al, 2008.…”
Section: Introductionmentioning
confidence: 99%